"ASKing" the Right Questions About Screening for Celiac Disease. (19th January 2021) - Forbes, Geoffrey M.
Abstract: Make a distinction between investigating symptoms and screening for disease. Understand the performance characteristics of a test for those with symptoms and for screening those without symptoms, whether at elevated risk or average risk of disease. Positive test results require patient education and follow-up. Importantly, screening should be advantageous to an individual, and disease treatment should be in their interest. The practical application of these principles in relation to population-based Celiac disease screening may be difficult, as a large Colorado study has found.